2014
DOI: 10.1155/2014/792536
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoniInfection and Associated Determinant Factors among School Children in Sanja Town, Northwest Ethiopia

Abstract: Background. Intestinal schistosomiasis is one of the most widespread parasitic infections in tropical and subtropical countries. Objective. To determine the prevalence of S. mansoni infection and associated determinant factors among school children in Sanja Town, northwest Ethiopia. Methods. A cross-sectional study was conducted from February to March, 2013. 385 school children were selected using stratified proportionate systematic sampling technique. Pretested questionnaire was used to collect sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
60
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 14 publications
21
60
9
Order By: Relevance
“…Our present study was lower than those research findings reported from different parts of Ethiopia such as from 89.9% from Saja towm, Northwest Ethiopia [7] , 85% in Zarim, 67% in Gorgora [8], 33.7% and 37.9% from northern Gonder [13,17], 73.9% from Southern Tigray [15] 81.3% from Wolita [10], 74.9% from Wondo Genet [11], 67.6% from Fincha valley Wollega [21] and 64.3% from Northwestern Tanzania [28]. This difference may be due to long endemicity of the parasites in the study area, sample size for the study, availability of the intermediate host in open water sources which the students have frequent contact with it ecological and climatic condition .…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Our present study was lower than those research findings reported from different parts of Ethiopia such as from 89.9% from Saja towm, Northwest Ethiopia [7] , 85% in Zarim, 67% in Gorgora [8], 33.7% and 37.9% from northern Gonder [13,17], 73.9% from Southern Tigray [15] 81.3% from Wolita [10], 74.9% from Wondo Genet [11], 67.6% from Fincha valley Wollega [21] and 64.3% from Northwestern Tanzania [28]. This difference may be due to long endemicity of the parasites in the study area, sample size for the study, availability of the intermediate host in open water sources which the students have frequent contact with it ecological and climatic condition .…”
Section: Discussioncontrasting
confidence: 90%
“…Based on this, bathing habits, washing clothes in open water sources and crossing rivers on bare foots were independent predictors for S. mansoni infection which is similar with finding reported from Gorgora town from North Gonder [16] Saja town Northwest Ethiopia [7] …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to those found in Nigeria [18, 32], in Kenya [38], in Yemen [24], and in Ethiopia [27, 29, 30]. …”
Section: Discussionsupporting
confidence: 90%
“…Among signi cantly associated factors observed, participants with high swimming frequencies and swimming habits had 2.3 times more rate of infection than those who had no habits. This was similar to studies which reported signi cant associations between parasitic infections and swimming practices and frequencies (30)(31)(32).…”
Section: Prevalence and Associated Risk Factors Of Intestinal Parasitsupporting
confidence: 91%